2002
DOI: 10.1016/s0045-6535(02)00145-5
|View full text |Cite
|
Sign up to set email alerts
|

Portal absorption of 14C after ingestion of spiked milk with 14C-phenanthrene, 14C-benzo[a]pyrene or 14C-TCDD in growing pigs

Abstract: Polycyclic aromatic hydrocarbons (PAHs) and dioxins are lipophilic organic pollutants occurring widely in the terrestrial environment. In order to study the PAHs and 2,3,7,8 TetraChloroDibenzo-pDioxin (TCDD) transfer in the food chain, pigs have been fed with milk mixed either with 14 Cphenanthrene, with 14 C-benzo[a]pyrene or with 14 C-TCDD. The analysis of portal and arterial blood radioactivity showed that both PAHs and TCDD were absorbed with a maximum concentration at 4-6 h after milk ingestion. Then, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…Using the Caco-2 cell model, Vasiluk et al [65] have demonstrated that uptake of B(a)P released into the gut lumen occurs through passive diffusion and its transfer into the bloodstream is aided by the fugacity gradient generated by the lipids. Additionally, works of Laurent et al [66,67] and Cavret et al [68] have shown a robust relationship between B(a)P and phenanthrene absorption and fat absorption. These studies reinforce the likelihood that prolonged exposure to B(a)P through dietary fat contributes to increased bioavailability of B(a)P and/or its metabolites in the GI tract and cause localized damage to the colon epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Using the Caco-2 cell model, Vasiluk et al [65] have demonstrated that uptake of B(a)P released into the gut lumen occurs through passive diffusion and its transfer into the bloodstream is aided by the fugacity gradient generated by the lipids. Additionally, works of Laurent et al [66,67] and Cavret et al [68] have shown a robust relationship between B(a)P and phenanthrene absorption and fat absorption. These studies reinforce the likelihood that prolonged exposure to B(a)P through dietary fat contributes to increased bioavailability of B(a)P and/or its metabolites in the GI tract and cause localized damage to the colon epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…The above findings suggest that portal venous transport of absorbed DMBA, probably as polar metabolites, is of much greater importance than lymphatic transport. Recent studies by Laurent et al (2002) and Cavret et al (2003) also demonstrated that transfer of labeled B[a]P and phenanthrene in pigs occur through absorption of portal system.…”
Section: Intestinal Metabolism Of Pahsmentioning
confidence: 99%
“…It readily distributes to soil and dust particles (Hattemer-Frey and Travis, 1991; Chung et al, 2011). The major routes of exposure are food, both due to endogenous contamination and cooking chemistry, as well as ambient air (indoor and outdoor) where vehicular exhaust and traditional combustion cooking and heating processes are the main source of BaP exposure aside from smoking (Mitchell, 1982; Wester et al, 1990; Laurent et al, 2002; Roseiro et al, 2011). Inhalation is the most effective route of BaP absorption, followed by ingestion, and then dermal uptake; however, the largest exposure is likely by ingestion (Wester et al, 1990; Hattemer-Frey and Travis, 1991; Edoardo, 1992; Laurent et al, 2002; Fromme et al, 2004; Moody et al, 2007).…”
Section: Introductionmentioning
confidence: 99%